PELATIHAN INOVASI PRODUK DAN PEMASARAN DIGITAL KRIPIK PISANG LUMER UNTUK PENGUATAN UMKM DESA TENGGERWETAN - Rofiah, Ulya Ainur; Widayati, Pipit; Umaroh, Siti Inayatul; Khotimah, Khusnul; Dul Khusna, Nur Akhid; Fatih, Ghufron Maulana; Herawati, Isti Indah (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This community service program was implemented in Tenggerwetan Village with the primary objective of improving the entrepreneurial capacity and technical skills of local residents through training in the production and marketing of kripik pisang lumer (creamy banana chips) based on local potential and religious tourism appeal. The activity targeted women’s community groups (PKK) and youth organizations (Karang Taruna) as strategic actors in strengthening the village’s UMKM sector. The training adopted a participatory and practice-oriented approach, combining interactive lectures, live production demonstrations, hands-on practice sessions, and simulations of branding and digital marketing strategies. Participants were introduced to innovative recipes, modern hygienic packaging methods, attractive label design, and online promotional techniques through social media platforms. The outcomes indicated a notable increase in participants’ competencies in both product innovation and business management. Furthermore, the program fostered greater awareness of branding as a tool for market competitiveness and facilitated collaboration between local entrepreneurs and community networks. In the long term, this initiative is expected to strengthen economic independence, create sustainable job opportunities, and enhance the visibility of Tenggerwetan Village as a center for locally based creative industries.